Sosialisasi Penggunaan Aplikasi Assemblr Edu Sebagai Media Pembelajaran Berbasis Augmented Reality Bagi Guru SDN Lonja - Nurul Fitriah Aras, Fitriah_arasss; Satria Dewi Pendit, Sinta; Lapasere, Sisriawan; Nur Isnayanti, Andi; Sukri (Jurnal Pengabdian Kepada Masyarakat Patikala, 2025)
The issues underlying the implementation of this community service activity cover two main aspects, namely: (1) the lack of optimal opportunities for teachers to develop their professional competencies through technology-based learning, and (2) the lack of maximum utilisation of learning media that is in line with the characteristics and learning styles of students. This community service activity was designed with the aim of improving teachers' understanding, skills, and competence in utilising the Assemblr Edu application as a means of designing Augmented Reality (AR)-based learning media. It is hoped that the implementation of this activity will make a real contribution to improving the quality of the learning process at SDN Lonja. The activity was carried out at SDN Lonja with the involvement of the principal and teachers based on the subjects they teach. The stages of implementation of the community service programme include socialisation and direct mentoring activities using a group approach, so that teachers can gain collaborative practical experience. The results of the activities show that all participants were able to use the Assemblr Edu application and create AR-based learning media tailored to the learning needs of each group, such as solar system and food chain visualisation media for upper grades, interactive maps for social studies and civics lessons, and 3D prayer and art media for religious and art teachers. The dissemination of the Assemblr Edu application to teachers proved to run smoothly and had a positive impact in the form of increasing teachers' knowledge and skills in using Augmented Reality (AR)-based learning media. Teachers who were initially unfamiliar with this application are now able to understand its benefits and operate it to create learning media in accordance with the teaching material. This activity has had a positive impact in improving teachers' readiness to face the challenges of 21st-century learning and has contributed to improving the quality of the teaching and learning process in schools.